Relationship between Work-life Balance, Burnout and Turnover Intention in Millennial Workers - Andi Nur Asri Ainun (Pascasarjana STIE Amkop Makassar, 2022)
This study will examine the effect of work-life balance and burnout on turnover intention in millennial workers in Makassar City. The type of research used in this research is quantitative research. The data in this study is primary data in the form of a questionnaire that has been distributed to 100 millennial workers. The sampling method used purposive sampling technique. Hypothesis testing was carried out using the SPSS 28.0 for windowa by testing the independent variables, namely work-life balance, burnout and the dependent variable, namely turnover intention. The results of the study show that work-life balance and burnout simultaneously have a significant effect on turnover intention. For the partial test, work-life balance has a negative and significant effect on turnover intention. Burnout has a positive and significant effect on turnover intention.Â Keywords : work-life balance, burnout, turnover intention